2021
DOI: 10.1002/adma.202103963
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Zn–Ag Catalyst Matrix and Electrolyzer System for CO2 Conversion to CO and Beyond

Abstract: year, [2] however carbon capture without utilization represents a purely sunken cost. Alternatively, CO 2 electrolysis provides a route to both environmental sustainability and economic viability by using clean electricity to electrochemically reduce waste CO 2 to generate a valueadded commodity. The field has made substantial breakthroughs in this area in recent years through adoption of gas diffusion electrodes (GDEs); [3] gas-porous supports that promote the mass transport of CO 2 from the gas phase to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Furthermore, these values only represent the conditions at a local slice in the gas channel, whereas experiments represent the average consumption over the entire channel (see SI Figure S7 for calculated internal CO 2(g) and electric current density profiles). In any case, it is encouraging that a rough comparison of Figure b to values experimentally extracted in Figure c and Figure c at similar current densities shows reasonable agreement without adjusting any parameters from Weng et al In terms of the functional dependence of the calculated k MT on CO 2 concentration in the gas channel, we hypothesize that the predicted rise in k MT at lower values of external CO 2(g) concentration in Figure b is due to increased (bi)­carbonate formation caused by an increase in pH at the cathode . In other words, as the CO 2(g) supply becomes limited, the pH-decreasing effect of CO 2 dissolution is lessened, which drives up the pH at the cathode and increases (bi)­carbonate formation.…”
supporting
confidence: 68%
“…Furthermore, these values only represent the conditions at a local slice in the gas channel, whereas experiments represent the average consumption over the entire channel (see SI Figure S7 for calculated internal CO 2(g) and electric current density profiles). In any case, it is encouraging that a rough comparison of Figure b to values experimentally extracted in Figure c and Figure c at similar current densities shows reasonable agreement without adjusting any parameters from Weng et al In terms of the functional dependence of the calculated k MT on CO 2 concentration in the gas channel, we hypothesize that the predicted rise in k MT at lower values of external CO 2(g) concentration in Figure b is due to increased (bi)­carbonate formation caused by an increase in pH at the cathode . In other words, as the CO 2(g) supply becomes limited, the pH-decreasing effect of CO 2 dissolution is lessened, which drives up the pH at the cathode and increases (bi)­carbonate formation.…”
supporting
confidence: 68%
“…At low flow rates the electrolyte floods the entire GDE, resulting in mass transport limitations and increased HER. It is unlikely that this flooding is occurring in the catalyst layer alone, as previous literature has demonstrated that the CO 2 diffusion layer thickness is on the order of microns rather than nanometers. We present in Figure the three idealized states in which a catalyst layer can exist. In reality it is likely that the true wetting of the catalyst layer occurs as a combination of all three idealized states.…”
mentioning
confidence: 99%
“…An electrochemical CO 2 reduction reaction (CO 2 RR) uses electrical energy to convert CO 2 molecules into hydrocarbon products, which can store the intermediate electricity as chemical energy in the form of fuels [ 1 ]. Various products, such as carbon monoxide [ 2 , 3 , 4 ], formic acid [ 5 , 6 ], methane [ 7 ], methanol [ 8 ], ethylene [ 9 , 10 ], acetic acid [ 11 ], ethanol [ 12 , 13 ], and minor C 3+ products [ 14 ], have been acquired from direct and homogeneously catalyzed CO 2 reduction. The selectivity of a specific product of the CO 2 RR is heavily dependent on the electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of a specific product of the CO 2 RR is heavily dependent on the electrocatalysts. Generally, Zn [ 4 ], Ag [ 2 ], and Pd [ 3 ] metals are extensively explored to produce CO, while Sn [ 5 ], Bi [ 5 ], and Pb [ 6 ] metals have been studied to generate HCOOH from the CO 2 RR. Other high-value products containing alcohols and olefins are difficult to obtain from the CO 2 RR owing to their multi-electron requirement, which is provided by the surface atomic arrangement of electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%